1987
DOI: 10.1007/bf02732052
|View full text |Cite
|
Sign up to set email alerts
|

Influence of experimental diabetes on brain levels of monoamine neurotransmitters and their precursor amino acids during tryptophan loading

Abstract: The variations in serum and brain concentrations of the large neutral amino acids and the simultaneous changes in brain levels of monoamine neurotransmitters have been studied in normal and streptozotocin-diabetic rats after tryptophan loading. An impaired acute accumulation of tryptophan and serotonin in the brain of diabetic rats was observed, concomitantly with a much faster disappearance of the administered tryptophan from the bloodstream in these animals than in controls. Following the tryptophan load, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Therefore, the infusion of L-Trp profoundly reduces brain influx of tyrosine (as shown in animal studies to about 40%, see Masiello et al 1987) and its availability for catechotamine synthesis. Indeed, decreased cerebrospinal fluid levels of dopamine and noradrenaline metabolites have been reported after the infusion of L-Trp in man and the same authors suggested that the neuroendocrine responses to L-Trp may more likely be mediated by decreased catecholaminergic activity instead of increased output of hypothalamic 5-HT terminals (van Praag et al 1987).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the infusion of L-Trp profoundly reduces brain influx of tyrosine (as shown in animal studies to about 40%, see Masiello et al 1987) and its availability for catechotamine synthesis. Indeed, decreased cerebrospinal fluid levels of dopamine and noradrenaline metabolites have been reported after the infusion of L-Trp in man and the same authors suggested that the neuroendocrine responses to L-Trp may more likely be mediated by decreased catecholaminergic activity instead of increased output of hypothalamic 5-HT terminals (van Praag et al 1987).…”
Section: Discussionmentioning
confidence: 96%
“…Secondly, we assessed whether the cerebral concentration of aromatic amino acids including tryptophan which may serve as precursors of neurotransmitter synthesis-in agreement with observations from experimental diabetes in rat [7,16,[18][19][20]-were also decreased in postmortem human brain tissue of deceased individuals with diabetes mellitus. An increased tryptophan-2,3-dioxygenase activity is known to occur in the liver of streptozotocin-diabetic rats resulting in an accelerated catabolism and clearance of tryptophan from the bloodstream [19,20].…”
Section: Discussionmentioning
confidence: 85%
“…An increased tryptophan-2,3-dioxygenase activity is known to occur in the liver of streptozotocin-diabetic rats resulting in an accelerated catabolism and clearance of tryptophan from the bloodstream [19,20]. The reduced level of tryptophan is considered as major factor leading to a decreased carrier-mediated uptake of tryptophan into the brain [7,16,20].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired accumulation of TRP in the brain concomitantly with a much faster disappearance of the administered TRP from the bloodstream was observed in streptozotocin-diabetic rats after TRP load (Masiello et al 1987 ). Surplus of dietary TRP, the initial substrate for the formation of KYN, KYNA, 3-HK, and 3H-KYNA, induces insulin resistance (IR), a precursor of T2D, in pigs (Koopmans et al 2009 ).…”
Section: Dysregulation Of Trp-kyn Metabolism In T2dmentioning
confidence: 98%